2020
DOI: 10.1016/j.marenvres.2020.105021
|View full text |Cite
|
Sign up to set email alerts
|

Year-round energy dynamics of sardine and anchovy in the north-western Mediterranean Sea

Abstract: Variability in body condition and energy storage has important implications for fish recruitment and ecosystem structure. Understanding strategies for energy allocation to maintenance, reproduction and growth is essential to evaluate the state of the fish stocks. In this study, we address the energetics dynamics of the annual cycle of anchovies (Engraulis encrasicolus) and sardines (Sardina pilchardus) in the northwestern Mediterranean Sea using indirect and direct condition indices. We assessed and validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 56 publications
(116 reference statements)
5
28
1
Order By: Relevance
“…Anchovy reproduces in spring and summer and obtains energy from feeding that is directly used for reproduction (Ganias, 2009;Giráldez, 2009). Seasonal variability in the body condition of anchovy tends to be less marked than in sardine (Albo-Puigserver et al, 2020), but the marked seasonality of the body condition of anchovy observed in the north suggest potential food limitations and the use of reserves for reproduction. Seasonal environmental patterns could partially explain differences in the phenology of life history traits.…”
Section: Latitudinalmentioning
confidence: 86%
See 2 more Smart Citations
“…Anchovy reproduces in spring and summer and obtains energy from feeding that is directly used for reproduction (Ganias, 2009;Giráldez, 2009). Seasonal variability in the body condition of anchovy tends to be less marked than in sardine (Albo-Puigserver et al, 2020), but the marked seasonality of the body condition of anchovy observed in the north suggest potential food limitations and the use of reserves for reproduction. Seasonal environmental patterns could partially explain differences in the phenology of life history traits.…”
Section: Latitudinalmentioning
confidence: 86%
“…Similar to our results, Giráldez and Abad (1995) also described different seasonal peaks of body condition in the south for anchovy. These differences in the seasonal pattern of body condition might play a key role in the dynamics of the reproduction of sardine, as this species accumulates energy during spring and summer for reproduction in autumn and winter (Albo-Puigserver et al, 2020). Low body condition before the start of the reproduction in October could have affected the quality of the spawning and ultimately the recruitment success in the northern area, as has been suggested for sardine off the coast of Portugal (Garrido et al, 2007).…”
Section: Latitudinalmentioning
confidence: 93%
See 1 more Smart Citation
“…Being low-cost, quick, and usually non-disruptive, these morphometric indices are used in many fields. Although their use have been validated for sardine and anchovy (Albo-Puigserver et al, 2020;Brosset et al, 2015a;Gatti et al, 2018a;McPherson et al, 2011), their utilization to infer energy content is still controversial (Davidson and Marshall, 2010;McPherson et al, 2011;Sardenne et al, 2016;Stevenson and Woods Jr, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, changes in hydrology modifying the mesoscale dynamics in the western Mediterranean waters would affect the distribution and abundance of the zooplankton communities via direct effects on their metabolism and/or by affecting different trophic levels of the food web. Such variations may be responsible for the increased frequency of jellyfish blooms (Bernard et al, 2011;Brotz and Pauly, 2012;Falkenhaug, 2014) or the decrease in the small pelagic fish (SPF) stocks observed in the Alboran and NW Mediterranean (MED) basins (Van Beveren, 2015;Brosset et al, 2016Brosset et al, , 2017Albo-Puigserver et al, 2020), with notable socioeconomic impacts on tourism and fisheries. Despite the suspected importance of zooplankton in the Spanish Mediterranean (Mercado et al, 2007;Saraux et al, 2019;Yebra et al, 2019), studies focused on determining which specific factors drive the variability patterns of zooplankton biomass and metabolic rates in these coastal waters are scarce (Herrera et al, 2014;Yebra et al, 2017bYebra et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%